Control of intestinal inflammation by regulatory T cells. - Singh, B; Read, S; Asseman, C; Malmström, V; Mottet, C; Stephens, L; Stepankova, R; Tlaskalova, H; Powrie, F (2001)
Transfer of CD4+ T cells to immune-deficient mice in the absence of the CD25+ subset leads to the development of colitis, indicating that regulatory cells capable of controlling a bacteria-driven inflammatory response are present in normal mice. Cells with this function are present in the thymus as well as in the periphery of germ-free mice, suggesting they may be reactive with self-antigen. These cells resemble CD4+CD25+ cells that inhibit organ-specific autoimmunity, suggesting that a similar subset of regulatory T cells may control responses to self and foreign antigens. Development of colitis is dependent on accumulation of activated CD134L+ dendritic cells (DC) in the mesenteric lymph nodes, which is inhibited by CD4+CD25+ cells, indicating that regulatory T cells may control DC activation in vivo. Whilst inhibition of T-cell activation in vitro by CD4+CD25+ cells does not involve interleukin-10 and transforming growth factor-beta, these cytokines are required for the suppression of colitis. It may be that control of responses that activate the innate immune system requires multiple mechanisms of immune suppression. Recently, we identified CD4+CD25+ cells with immune suppressive activity in the thymus and peripheral blood of humans, raising the possibility that dysfunction in this mechanism of immune regulation may be involved in the development of autoimmune and inflammatory diseases.